(untitled) (Journal of the College of Basic Education, 2022)
It is not possible to research historical discourses without epistemological excavations that examine the roots of these discourses and the structure of social, political and economic interaction that is attached to their formulations, as seen by (Michel Foucault) (), who formulated the history of things through what is essential and marginal, but sometimes he is not mentioned in determining the process of these discourses. Here, he does not stray far from the Marxist approach in seeing the historical process through the superstructures and their connections to the substructures, where the cultural product remains an expression of the live interaction of these structures.